RETRACTED: Study of the correlation dependence of complications in the organization of medication support when using cilostazol drugs as complex therapy for diabetic foot syndrome - Koreyba K.A.; Dibirov M.D.; Gadzhimuradov R.U.; Koreiba D.K. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001